Cyclodextrin production in hollow fiber membrane reactor system: effect of substrate preparation - Mimi Sakinah, A. M.; Ismail, Ahmad Fauzi; Mohd Illias, Rosli; Zularisam, A. W.; Hassan, O.; Matsuura, T. (Elsevier B.V., 2008)

(untitled)
Production and separation of cyclodextrins (CDs) were assessed by employing an enzymatic membrane reactor (EMR) system. Comparison between gelatinized and ungelatinized tapioca starch was conducted to identify the pre-eminent type of tapioca starch via its reaction kinetic and the behavior of the ultrafiltration membrane in an EMR system. Results showed that the Michaelis constant value (Km) for gelatinized tapioca starch was 47% lesser than the ungelatinized tapioca starch, which indicates higher affinity and strong substrate binding with the employed cyclodextrin glycosyltransferase (CGTase). However, gelatinized tapioca starch generated high membrane fouling, which demonstrated 60% higher hydraulic resistances and 7% lower percentage of flux recovery than ungelatinized tapioca starch, due to the cake deposition associated with large swollen tapioca starch molecules